The Mapping of Development Strategy of Religious and Moral Values for Early Childhood in PAUD Kuok District, Kampar Regency - N, Zulkifli; Febrialismanto, Febrialismanto (Proceedings of the UR International Conference on Educational Sciences, 2018)
The aim of this research was to describe the strategy and achievement in the level of early childhood development in aspects of religious and moral values by teachers in early childhood education (PAUD) Kuok Sub district, Kampar. Meanwhile, the research methodology used was a survey in the form of quantitative descriptive.The finding of this study shows that the achievement of the level of early childhood development for ages 4-6 years, from 6 indicators, it can be seen the majority of children are in the category of developing according to expectations (BSH = 65.50%) and developing very well (BSB = 11, 36%). Most of PAUD teachers in Kuok Subdistrict Kampar often and very often used 11 strategies in developing religious and moral values for children age of 4-6 years, in fact the results are effective to develop religious and moral values for children age 4-6 years in PAUD Kuok District, Kampar District. Further research is needed towards the application of strategies for developing religious and moral values for children aged 4-6 years in PAUD in the context of local wisdom.